Differences Between US and UK Adults in Stroke Preparedness: Evidence From Parallel Population-Based Community Surveys. Issue 11 (November 2015) - Dombrowski, Stephan U.; Ford, Gary A.; Morgenstern, Lewis B.; White, Martin; Sniehotta, Falko F.; Mackintosh, Joan E.; Gellert, Paul; Skolarus, Lesli E.
Abstract : Background and Purpose—: Although time-dependent treatment is available, most people delay contacting emergency medical services for stroke. Given differences in the healthcare system and public health campaigns, exploring between-country differences in stroke preparedness may identify novel ways to increase acute stroke treatment. Methods—: A survey was mailed to population-based samples in Ingham County, Michigan, US (n=2500), and Newcastle upon Tyne, UK (n=2500). Surveys included stroke perceptions and stroke/nonstroke scenarios to assess recognition and response to stroke. Between-country differences and associations with stroke preparedness were examined using t tests and linear mixed models. Results—: Overall response rate was 27.4%. The mean age of participants was 55 years, and 58% were female. US participants were better in recognizing stroke (70% versus 63%, d=0.27) and were more likely to call emergency medical services (55% versus 52%, d=0.11). After controlling for demographics and comorbidities, US participants remained more likely to recognize stroke but were not more likely to respond appropriately. A greater belief that medical treatment can help with stroke and understanding of stroke was associated with improved stroke recognition and response. Conclusions—: Overall, stroke recognition and response were moderate. US participants were modestly better at recognizing stroke, although there was little difference in response to stroke. Future stroke awareness interventions could focus more on stroke outcome expectations and developing a greater understanding of stroke among the public.